Semissíntese de derivados de moléculas biologicamente ativas obtidas de plantas e microrganismos da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The Amazon rainflorest has described by its fauna, flora and microbiota, arousing interest of researchers for this region aggregated knowledge. Such interest is regarding the new findings saying that Amazon has an incredible biodiversity, where new molecules with potential for new drugs are often reported. Among the alternatives to existing drugs in the market is semisynthesis of organic molecules. In this work all semisynthesis were made from secalonic acids, isocoumarin bergenin and triterpene polycarpol. Those bioactive substances where isolated in advance from a microorganism and plants from Amazon. Through simple structural modification reactions, nine compounds were obtained and identified as: dibenzyl secalonic acid, dibenzyl bergenin, 15-O-benzoyl-polycarpol, 24-epoxy-polycarpol, 3-acetyl-policarpol, 15-acetyl-polycarpol, 3,15-diacetyl-polycarpol, 2,6,12,15-tetroxide-polycarpol. Additionally the reaction intermediate O-acyldicicloexylisoureia has been isolated and characterized. This intermediate and polycarpol derivatives are unprecedented in the literature.
Keywords: Semissíntese; Policarpol; Bergenina; Ácido Secalônico; Semisynthesis; Secalonic acid; Bergenin; Policarpol; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA: QUÍMICA ORGÂNICA